2017
DOI: 10.26912/sdj.2017.01.01-02
|View full text |Cite
|
Sign up to set email alerts
|

Level of salivary uric acid in gingivitis and periodontitis patients

Abstract: Background: Periodontal disease is common chronic adult condition. Antioxidants are present in the body fluid as protection against free radical. Uric acid is one of antioxidants that can be found in saliva. Moreover, the relationship among the antioxidant enzymes activities and clinical periodontal status were investigated. Objectives: The aim of the study was to observe uric acid level activities in the saliva of gingivitis and periodontitis patients. Methods: Six patients with gingivitis and six patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 7 publications
(4 reference statements)
1
9
0
Order By: Relevance
“…Smokers with periodontitis show lower levels of uric acid than nonsmokers with periodontitis and much lower levels than periodontally healthy individuals, suggesting that uric acid is an oxidative stress marker (Fatima et al, 2016). In contrast, salivary uric acid levels were found to be higher in periodontitis patients than in gingivitis patients (Rizal & Vega 2017). The level of plasma uric acid in chronic periodontitis patients was found to be significantly increased compared with that in healthy individuals (Banu et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Smokers with periodontitis show lower levels of uric acid than nonsmokers with periodontitis and much lower levels than periodontally healthy individuals, suggesting that uric acid is an oxidative stress marker (Fatima et al, 2016). In contrast, salivary uric acid levels were found to be higher in periodontitis patients than in gingivitis patients (Rizal & Vega 2017). The level of plasma uric acid in chronic periodontitis patients was found to be significantly increased compared with that in healthy individuals (Banu et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…Among the virulence factors of P. gingivalis , gingipains consisting of two arginine‐specific proteases (RgpA and RgpB) and a lysine‐specific protease (Kgp) have multiple functions that dysregulate the host immune response (Curtis et al, 1999; Guo et al, 2010). A higher level of uric acid has been detected in the plasma of chronic periodontitis patients than in the plasma of healthy control individuals (Banu et al, 2015) and gingivitis patients (Rizal & Vega 2017). In our previous study, we found that P. gingivalis induces uric acid release in THP‐1 macrophages (Jun et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Future research is needed to fully examine the sensitivity of sUA concentrations to these methodologic and oral-specific confounds. The investigation of oral health and its associations with sUA, GDM, and hypertensive risk is especially important as sUA levels may vary by periodontal disease status and these effects may be different for hypertensive or preeclamptic women (54,73,74).…”
Section: Limitationsmentioning
confidence: 99%
“…We anticipated lower sUA levels in earlier pregnancy than in later pregnancy (37), and that maternal body mass index (BMI) and age would be positively associated with sUA levels while the duration of sleep the prior night would show inverse associations with sUA (20,52). The importance of other maternal and saliva sample characteristics, such as maternal education, socioeconomic status, race/ethnicity, prior pregnancies, medication use, oral health, and salivary flow rate, in predicting sUA concentrations and/or confounding the relations of interest in the study were explored based on prior work (14,20,(53)(54)(55). Finally, we expected excessive weight gain and hypertension during pregnancy would be positively associated with sUA levels.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, uric acid levels in periodontitis patients have been found to be higher than in gingivitis patients. Moreover, uric acid has many roles in periodontitis than in gingivitis as an antioxidant agent [32].…”
Section: Uric Acidmentioning
confidence: 99%